Homozygous C677T mutation of the 5,10-methylenetetrahydrofolate reductase gene with hyperhomocysteinaemia associated with lupus anticoagulant in a chronic peritoneal dialysis patient with cerebral venous thrombosis- Case Report - Guimaraes, Nuno; Silva, Sónia; Branco, Patrícia; Almeida, Edgar de; Canhão, Patrícia; Barbas, José; Gomes da Costa, A.; Prata, M. Martins (SPN - Sociedade Portuguesa de Nefrologia, 2008)
We report a case of a cerebral venous thrombosis (CVT) in a chronic kidney disease patient with three CVT predisposing conditions. A 53 year-old woman on chronic peritoneal dialysis presented to the emergency department with acute headache and vertigo. The neurological examination and head CT scan performed at the emergency department were normal but, three days later, a lateral gait deviation and a horizontal nystagmus were identified. A brain MRI and MRI-venogram confirmed a left lateral sinus thrombosis. Hormonal replacement therapy (HRT), a positive lupus anticoagulante and a homozygous mutation on the methylenetetrahydrofolate reductase gene, with hyperhomocysteinaemia, were the three well-known prothrombotic conditions identified in this patient. HRT was discontinued, the patient started anticoagulation with warfarin and folic acid supplementation and was discharged, 10 days after admission, complaining of a mild vertigo. After six months of therapy the patient had vertigo improvement and maintained a positive lupus anticoagulant. The head MRI and MRI-venography showed a thrombus reduction.
Case Report
Keywords: cerebral venous thrombosis; hyperhomocysteinaemia; lupus anticoagulant; peritoneal dialysis; Madeira Island; Portugal; left lateral sinus thrombosis